PEMANFAATAN LIMBAH ABU SERBUK KAYU SEBAGAI MATERIAL PENGISI CAMPURAN LATASTON TIPE B - Sabaruddin, Sabaruddin (Jurnal Transportasi, 2011)
The waste of sawdust ash available in Ternate, North Maluku Province, has the potential to be used as material for making asphalt concrete mixtures. In this study, the waste of sawdust ash was used to make a mixture of type B Hot Rolled Sheet Asphalt Concrete (HRS). The results showed that sawdust ash has the potential to be used as the filler material in the mixture of type B HRS. It was shown also that the voids in mixture of the type B HRS in this study were very high, which could reduce the durability of the mixture. The use of sawdust ash has also the potential to produce cheaper mixtures.Key words: sawdust ash, hot rolled sheet, voids in the mix, durability.